Ensino Religioso: aspecto legal e curricular - Stigar, Robson (Último Andar)
JUNQUEIRA, Sérgio Rogério Azevedo; CORRÊA, Rosa Lydia Teixeira; HOLANDA, Ângela Maria Ribeiro. Ensino Religioso: aspectos legal e curricular. São Paulo: Paulinas, 2007.